المشاركة السياسية لطلبة كلية التربية الأساسية بدولة الكويت: دراسة ميدانية - العجمي، حجاج مبارك حجاج Alajami, Hajjaj Mubarak Hajjaj; العجمي، ناصر مسلم; الرشيدي، براك صنت عايض (جامعة الأزهر - كلية التربية, 2016)
The study aimed at exploring the degree of political participation for students of College of Basic Education in Kuwait and to achieve the goal of the study was designed for that, it composed of a (24) closed question, about political participation within and attention the university and outside, to political matters in general, can was mate sure of validity and reliability, and then applied a the sample consisted of (972) students, (324) male and (648) female, and after processing the data statistically redings were ready to be presented findings neveld the following: a lack of political participation within the college for both sexes hitting percentage (51%), as well as the weakness of political participation nate outside the university (51.9%) for males and (27.9%) for females, and the results showed a lack of interest of students concerning political news, and the presence of negative attitudes towards party work in general. In light of the findings, the study made a number of recommendations.
هدفت الدراسة إلى الكشف عن درجة المشاركة السياسية لطلبة كليه التربية الأساسية بدولة الكويت، ولتحقيق هدف الدراسة تم تصميم استبانة تكونت من (24) سؤالا مغلقا، حول المشاركة السياسية داخل الكلية وخارجها، والاهتمام بالأمور السياسية بشكل عام، وتم التأكد من صدقها وثباتها، وتم تطبيقها على عينة مكونة من (972) طالبا وطالبة،(324) من الذكور، و(648)من الإناث، وبعد معالجة البيانات إحصائيا، توصلت الدراسة وفى مجموعة من النتائج كان من أهمها: ضعف المشاركة السياسية داخل الكلية لدى الجنسين إذ بلغت النسبة الكلية (51%)، وكذلك ضعف المشاركة السياسية خارج الجامعة إذ بلغت (51.9%) للذكور، و(27.9%) للإناث، كما بينت النتائج عدم اهتمام الطلبة بالأخبار السياسية، ووجود اتجاهات سلبية نحو العمل الحزبي بشكل عام. وفي ضوء النتائج قدمت الدراسة عددا من التوصيات الإجرائية المستقبلية.
Keywords: الكويت -- طلبة الجامعة -- كلية التربية الأساسية -- المشاركة السياسية